Assessment of smoking care by stroke specialists in patients with recent TIA and minor stroke: an international prospective registry-based cohort study - Lavallée, Philippa; Charles, Hugo; Labreuche, Julien; Albers, Gregory W.; Caplan, Louis; Donnan, Geoffrey A.; Ferro, José Manuel; Hennerici, Michael G.; Molina, Carlos A.; Rothwell, Peter; Steg, Gabriel; Touboul, Pierre-Jean; et al. (BMJ open, 2024)
Objectives The objectives are to assess smoking abstinence and its effects on vascular risk and to report tobacco-cessation counselling and pharmacotherapy use in patients who had a recent minor stroke or transient ischaemic attack (TIA). - Design and setting The TIA registry.org project is a prospective, observational registry of patients with TIA and minor stroke that occurred in the previous 7 days with a 5-year follow-up, involving 61 sites with stroke specialists in 21 countries (Europe, Asia, Latin America and Middle East). Of those, 42 sites had 5-year follow-up data on more than 50% of their patients and were included in the present study. - Participants From June 2009 through December 2011, 3847 patients were eligible for the study (80% of the initial cohort). - Outcomes Tobacco counselling and smoking-cessation pharmacotherapy use in smoking patients were reported at discharge. Association between 3-month smoking status and risk of a major cardiovascular event (MACE) was analysed with multivariable Cox regression model. - Results Among 3801 patients included, 835 (22%) were smokers. At discharge, only 35.2% have been advised to quit and 12.5% had smoking-cessation pharmacotherapy prescription. At 3 months, 383/835 (46.9%) baseline smokers were continuers. Living alone and alcohol abuse were associated with persistent smoking; high level of education, aphasia and dyslipidaemia with quitting. The adjusted HRs for MACE at 5 years were 1.13 (95% CI 0.90 to 1.43) in former smokers, 1.31 (95% CI 0.93 to 1.84) in quitters and 1.31 (95% CI 0.94 to 1.83) in continuers. Using time-varying analysis, current smoking at the time of MACE non-significantly increased the risk of MACE (HR 1.31 (95% CI 0.97 to 1.78); p=0.080). - Conclusion In the TIAregistry.org, smoking-cessation intervention was used in a minority of patients. Surprisingly, in this population in which, at 5 years, other vascular risk factors were well controlled and antithrombotic treatment maintained, smoking cessation non-significantly decreased the risk of MACE.